Wind turbine control in computational fluid dynamics with OpenFOAM. Issue 4 (August 2017) - Daniele, Elia
In this article, the implementation of the pitch-control option is described within the OpenFOAM computational fluid dynamics library supported by the preliminary results for a few representative test cases. The proposed pitch-control logic represents a simplified version of the typically model available for the load simulation based on blade element momentum theory codes. The control variable for the blade pitch regulation is the rotor rotational speed, for which an additional torque-speed controller determining the equilibrium between the aerodynamic and the electrical torque is required. The simulations are performed on the 80-m-diameter turbine used as a reference design within the SmartBlades project. The unsteady test cases are based on the assumption of rigid, not pre-bend blade, and refer to an emergency stop and an extreme operating gust. Results verified the correctness of the implemented control logic and its sensitivity to the control parameters, that is, the key factors for a successful regulation of power production and load mitigation in wind turbine design. The implemented simulation methodology constitutes the first step toward the reproduction of very complex operating conditions for wind turbines by means of accurate computations.